EFFECTS OF FEDERAL CONSTITUTIONAL GRANTS IN BRAZILIAN MUNICIPALITIES. Issue 3 (7th October 2019) - Ferreira, Lucas Oliveira Gomes; Serrano, André Luiz Marques; Revelli, Federico
Abstract : The objective of the present study is to verify the flypaper effect of 476 Brazilian municipalities from 2005 to 2012, considering the new variables as instruments of grants. Political alignment, alignment of the party, and coalition of the mayor with the federal president and of the state governor were considered as instruments of grants. A municipal tax autonomy index was considered as a control variable, which represents the percentage of local taxes in the municipal total revenues. The results allow concluding that the flypaper effect exists in Brazilian municipalities and is intensified by the alignment of the representatives in the same way of theoretical literature (Hamilton 1983; Hines & Thaler 1995; Inman 2008) and previous empirical studies in Brazil. Moreover, evidences of higher flypaper effect were found in municipalities with low tax autonomy.